Sediment Connectivity: A Framework for Analyzing Coastal Sediment Transport Pathways. Issue 10 (24th October 2020) - Pearson, Stuart G.; van Prooijen, Bram C.; Elias, Edwin P. L.; Vitousek, Sean; Wang, Zheng Bing
Abstract: Connectivity provides a framework for analyzing coastal sediment transport pathways, building on conceptual advances in graph theory from other scientific disciplines. Connectivity schematizes sediment pathways as a directed graph (i.e., a set of nodes and links). This study presents a novel application of graph theory and connectivity metrics like modularity and centrality to coastal sediment dynamics, exemplified here using Ameland Inlet in the Netherlands. We divide the study site into geomorphic cells (i.e., nodes) and then quantify sediment transport between these cells (i.e., links) using a numerical model. The system of cells and fluxes between them is then schematized in a network described by an adjacency matrix. Network metrics like link density, asymmetry, and modularity quantify system‐wide connectivity. The degree, strength, and centrality of individual nodes identify key locations and pathways throughout the system. For instance, these metrics indicate that under strictly tidal forcing, sand originating near shore predominantly bypasses Ameland Inlet via the inlet channels, whereas sand on the deeper foreshore mainly bypasses the inlet via the outer delta shoals. Connectivity analysis can also inform practical management decisions about where to place sand nourishments, the fate of nourishment sand, or how to monitor locations vulnerable to perturbations. There are still open challenges associated with quantifying connectivity at varying space and time scales and the development of connectivity metrics specific to coastal systems. Nonetheless, connectivity provides a promising technique for predicting the response of our coasts to climate change and the human adaptations it provokes. Plain Language Summary: The pathways that sand takes as it moves along coasts and estuaries are determined by a complex combination of waves, tides, geology, and other environmental or human factors. These pathways can be challenging to analyze and predict using existing approaches, so we turn to the concept of connectivity. Connectivity represents the pathways that sediment takes as a series of nodes and links, much like in a subway or metro map. This approach is well used in other scientific fields, but in this study we apply these techniques to a new research field: coastal sediment dynamics. To demonstrate the sediment connectivity approach, we use it to map sediment pathways at a coastal site in the Netherlands. The statistics computed using connectivity let us quantify and visualize these sediment pathways, revealing new insights into the coastal system. We can also use this approach to address practical engineering questions, such as where to place sand nourishments for coastal protection. Sediment connectivity thus provides a promising technique for predicting the response of our coasts to climate change and the human adaptations it provokes. Key Points: Connectivity schematizes sediment transport pathways as a directed graph (series of nodes and links) We present a novel application of graph theory and network analysis to characterize complex coastal systems Example of Ameland Inlet demonstrates usefulness of connectivity in real‐world applications